2010
DOI: 10.1021/jm1013105
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (7R)-14-Cyclohexyl-7-{[2-(dimethylamino)ethyl](methyl) amino}-7,8-dihydro-6H-indolo[1,2-e][1,5]benzoxazocine-11-carboxylic Acid (MK-3281), a Potent and Orally Bioavailable Finger-Loop Inhibitor of the Hepatitis C Virus NS5B Polymerase

Abstract: Infections caused by hepatitis C virus (HCV) are a significant world health problem for which novel therapies are in urgent demand. The polymerase of HCV is responsible for the replication of viral genome and has been a prime target for drug discovery efforts. Here, we report on the further development of tetracyclic indole inhibitors, binding to an allosteric site on the thumb domain. Structure-activity relationship (SAR) studies around an indolo-benzoxazocine scaffold led to the identification of compound 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 71 publications
0
38
0
Order By: Relevance
“…11 Internal analysis of published clinical data sets of HCV NNIs showed correlation between the maintenance of NNI inhibitor concentrations above the protein adjusted EC 90 value and declines in HCV RNA levels (data not shown), therefore, the protein adjusted EC 90 for genotype 1b NS5B C316N replicon PA EC 90 (124 nM ¼ 69 ng/mL) was selected as the minimum target exposure at which antiviral activity was like to occur. [22][23][24][25][26][27][28] The similar in vitro potencies of these compounds and the predictions made by Reddy et al suggested the desired drop in viral load would require substantially higher and more frequent GSK2485852 doses so plasma concentrations many multiples above the PA EC 90 would be maintained in the majority of subjects. HCV-infected subjects exposed to the 420 mg dose had GSK2485852 concentrations that exceeded the PA EC 90 for 7.4-16 hours and had significant decline of À1.33 log 10 IU/ mL in HCV RNA levels.…”
Section: Discussionmentioning
confidence: 87%
“…11 Internal analysis of published clinical data sets of HCV NNIs showed correlation between the maintenance of NNI inhibitor concentrations above the protein adjusted EC 90 value and declines in HCV RNA levels (data not shown), therefore, the protein adjusted EC 90 for genotype 1b NS5B C316N replicon PA EC 90 (124 nM ¼ 69 ng/mL) was selected as the minimum target exposure at which antiviral activity was like to occur. [22][23][24][25][26][27][28] The similar in vitro potencies of these compounds and the predictions made by Reddy et al suggested the desired drop in viral load would require substantially higher and more frequent GSK2485852 doses so plasma concentrations many multiples above the PA EC 90 would be maintained in the majority of subjects. HCV-infected subjects exposed to the 420 mg dose had GSK2485852 concentrations that exceeded the PA EC 90 for 7.4-16 hours and had significant decline of À1.33 log 10 IU/ mL in HCV RNA levels.…”
Section: Discussionmentioning
confidence: 87%
“…Quasispecies population before and after treatment as well as selection of mutations leading to the appearance of resistant variants were also analyzed by ultra deep sequencing in these animals (Shi et al, 2013). Furthermore, several other compounds with an effect on viral replication have also been tested with success as monotherapy against HCV infection (Nakagawa et al, 2007; Kneteman et al, 2009; Narjes et al, 2011). …”
Section: Rodent Models Of Hcv Infectionmentioning
confidence: 99%
“…16 To rule out any bias, each of the five reported NS5B allosteric binding pockets TP-I (PDB ID: 2XWY), 11 TP-II (PDB ID: 3FRZ), 12 PP-I (PDB ID: 3TYV) 27 , PP-II (PDB ID: 3FQL), 14 and PP-III, that significantly overlaps with PP-II (large grid box created around PP-II bound HCV-796 to obtain docking pose at PP-III), was examined for inhibitor binding. Analysis of the binding energy data (Glidescores) for all single digit µM inhibitors at each allosteric site revealed that they bind with affinity in the order PP-I>PP-II>PP-III>TP-I>TP-II.…”
Section: Resultsmentioning
confidence: 99%
“…3D Structures of target compounds 17–39 and 41–45 were constructed using the fragment dictionary of Maestro 9.0 (Schrodinger, LLC, New York, NY) and geometry was optimized by Macromodel program v9.5 using the OPLS-AA force field with the steepest descent followed by truncated Newton conjugate gradient protocol. The X-ray crystal structure of NS5B polymerase in complex with MK-3281 (PDB ID: 2XWY) 11 , with PF-868554 (PDB ID: 3FRZ) 12 , with indole C2-acyl sulfonamide (PDB ID: 3TYV) 27 , with HCV-796 (PDB ID: 3FQL) 14 and palm pocket (PP)-III, that significantly overlaps with PP-II (large grid box created around PP-II bound HCV-796 to obtain docking pose at PP-III) representing thumb pocket (TP)-I, TP-II, palm pocket (PP)-I, PP-II and PP-III pockets, respectively, obtained from the RCSB Protein Data Bank (PDB), were used in this study. The protein was optimized for docking using the “Protein Preparation Wizard” and “Prime-Refinement Utility” of Maestro 9.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation